Adat as a local ideology of indigenous people in political event - Sukri Tamma; Timo Markus Duile; Ramlah Daud (ETNOSIA : Jurnal Etnografi Indonesia, 2020)
This article aims to show the phenomenon of Adat as an influential factor in Indonesia's regional election process after the New Order Era. The phenomenon seems to indicate a "local ideology" that fundamentally influences people's political behavior within regional elections. Based on the regional election was in the Toraja regions, Province of South Sulawesi in 2015, this article intends to shows how Adat as the Toraja ethnic group foundation of social identity became the fundamental standard of political behavior. It seems to present Adat as an ideology for the ethnic group where dominantly during the regional election. Ultimately, the view from the Toraja regional election has indicated the possibility of local ideology existence where could be crucial for the local political dynamics. It means the ideology as part of political behavior standard is not only present in its general form as known today. Certain communities could have local ideologies based on their local wisdom, and their context was strictly related to efforts to keep their existence as indigenous people as well as their reclaim as the owner of the land.